2018
DOI: 10.4236/jbbs.2018.82004
|View full text |Cite
|
Sign up to set email alerts
|

Non-Painful Peripheral Inflammation Blocks Conditioned Place-Preference to Morphine and Nicotine through an Ibuprofen-Sensitive and an Ibuprofen Insensitive Pathway

Abstract: The field of neuroimmunology has expanded in recent years providing new insights and therapies into pathologies like stroke, autism, and depression. However, few works explore the relationship between inflammatory stimuli and motivation. Thus, the aim of this study was to determine how non-painful inflammatory stimuli affect reward. To test reward-response, we used the morphine and the nicotine induced conditioned place-preference and placeaversion model in rats with non-painful inflammation. The following inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…This reduction significantly inhibited the opioid-induced reward [32]. Later, we reported the non-painful carrageenan induced inflammation had protective effects to morphine-induced conditioned place preference [13]. Additionally, we found this effect was reversed by administering a cyclooxygenase inhibitor.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This reduction significantly inhibited the opioid-induced reward [32]. Later, we reported the non-painful carrageenan induced inflammation had protective effects to morphine-induced conditioned place preference [13]. Additionally, we found this effect was reversed by administering a cyclooxygenase inhibitor.…”
Section: Discussionmentioning
confidence: 51%
“…However, we recently found that carrageenan-induced painless inflammation is responsible for blocking morphine reward behavior. Moreover, the administration of ibuprofen significantly increases reward behavior and at the same time blocks the inflammation processes [13]. We speculate that the cause for this is related to the increase of pro-inflammatory molecules which is induced by carrageenan administration and modulated by administering ibuprofen.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation